2016
DOI: 10.1080/13607863.2016.1191057
|View full text |Cite
|
Sign up to set email alerts
|

The role of compassion, suffering, and intrusive thoughts in dementia caregiver depression

Abstract: Objectives Exposure to suffering of a relative or friend increases the risk for psychological and physical morbidity. However, little is known about the mechanisms that account for this effect. We test a theoretical model that identifies intrusive thoughts as a mediator of the relation between perceived physical and psychological suffering of the care recipient and caregiver depression. We also assess the role of compassion as a moderator of the relation between perceived suffering and intrusive thoughts. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 40 publications
1
27
0
1
Order By: Relevance
“…Other stressors and strains that have been found to impact well-being include strain from the disease itself (e.g. extent of cognitive impairment) (Buckley et al, 2012, Dawson et al,2013, Logsdon et al, 2002), relationship strain or poor relationship quality between the CP and PWD (Häusler et al, 2016, Fauth et al, 2012, Moon et al, 2016), the CP’s perceptions of physical and psychological suffering in the PWD (Schulz et al, 2017), and the amount of difficulty the CP has in finding meaning in providing care to the PWD (Quinn et al, 2010).…”
Section: Stressors and Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other stressors and strains that have been found to impact well-being include strain from the disease itself (e.g. extent of cognitive impairment) (Buckley et al, 2012, Dawson et al,2013, Logsdon et al, 2002), relationship strain or poor relationship quality between the CP and PWD (Häusler et al, 2016, Fauth et al, 2012, Moon et al, 2016), the CP’s perceptions of physical and psychological suffering in the PWD (Schulz et al, 2017), and the amount of difficulty the CP has in finding meaning in providing care to the PWD (Quinn et al, 2010).…”
Section: Stressors and Strainsmentioning
confidence: 99%
“…Dementia is often considered to be a threat to an individual’s well-being, whether that individual is the person who receives a dementia diagnosis (Stites et al, 2017, Orgeta et al,2015,Nagpal et al, 2014) or the family member who provides the majority of informal dementia care (Schulz et al, 2017, Cunningham et al, 2018). Multiple stressors and strains arising from the dementia context have been examined for their potential to threaten the well-being of either the person with dementia (PWD) or the family care partner (CP) (Buckley et al, 2012, Fauth et al, 2012, Judge et al, 2010).…”
mentioning
confidence: 99%
“…Compassion is an important and necessary element in providing professional patient care [1]. Health care professionals such as nurses are regularly exposed to contact with violence, suffering and death.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that caregivers who had greater compassion reported more intrusive thoughts even when perceived physical suffering of the demented older person was low. Being a highly compassionate caregiver has negative effects, although higher levels of caregiver compassion likely reflect a high‐quality relationship with the demented older person and is an important factor in the caregiving process (Schulz, Savla, Czaja, & Monin, ).…”
Section: Introductionmentioning
confidence: 99%